2017
DOI: 10.1111/pcn.12623
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, 8‐week, double‐blind, placebo‐controlled trial of vortioxetine in Japanese adults with major depressive disorder, followed by a 52‐week open‐label extension trial

Abstract: Vortioxetine failed to meet significance versus placebo in the primary efficacy analysis at week 8 in the short-term study. The extension trial indicated continued improvement of depressive symptoms from baseline of this study throughout the 52-week treatment period. Vortioxetine treatment was safe and well tolerated in both studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…The safety profile of vortioxetine in this study is consistent with other studies in both Japanese and non‐Japanese patients; the most common adverse events were gastrointestinal in nature with participants reporting an increased prevalence of nausea and vomiting compared with placebo, although the adverse events were generally mild or moderate in intensity . The prevalence of somnolence was low and also consistent with other studies .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The safety profile of vortioxetine in this study is consistent with other studies in both Japanese and non‐Japanese patients; the most common adverse events were gastrointestinal in nature with participants reporting an increased prevalence of nausea and vomiting compared with placebo, although the adverse events were generally mild or moderate in intensity . The prevalence of somnolence was low and also consistent with other studies .…”
Section: Discussionsupporting
confidence: 90%
“…The safety profile of vortioxetine in this study is consistent with other studies in both Japanese and non‐Japanese patients; the most common adverse events were gastrointestinal in nature with participants reporting an increased prevalence of nausea and vomiting compared with placebo, although the adverse events were generally mild or moderate in intensity . The prevalence of somnolence was low and also consistent with other studies . Vortioxetine has generally been associated with a lower prevalence of TEAE, including sexual dysfunction and TEAE leading to discontinuation, compared with other antidepressants (duloxetine and extended‐release venlafaxine) in head‐to‐head studies .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consequently, weight‐neutral treatments should be the focus of future antidepressant developments. Clinical trials have suggested that ketamine and vortioxetine may be efficacious options for the treatment of MDD with minimal effects on weight (94,104) . Currently, there are no metabolic monitoring guidelines for antidepressants (compared with antipsychotics that have well‐established guidelines), and given the high risk of weight‐change effects with some agents, we should adopt similar monitoring guidelines for antidepressants balanced with resource utilization.…”
Section: Resultsmentioning
confidence: 99%